A new combined quasigeoid model in Tierra del Fuego - Gomez, María Eugenia (2014)
This work focuses on the development of a combined quasigeoid model for Tierra del Fuego province. The Equivalent Source Technique (EST) is applied together with the remove-compute-restore technique in order to combine gravity and GPS/levelling observations and to obtain a quasigeoid model. This model features an improved accuracy in relation to previous models. A discussion about the geodetic reference system is also presented. Geodetic coordinates of all stations used were transformed to TDF08 to be in accordance with the new geodetic reference frame of Argentina. After a cross validation procedure it is determined that a 5cm (r.m.s.) quasigeoid model has been achieved for the major part of the province, fulfilling the requirements for its practical use. New Global Geopotential Models (GGM) are introduced in the discussion, particularly the EGM2008 which is used for evaluation purposes. It shows a 9cm agreement after its evaluation on the levelling lines.